Karbon Aktif Berbahan Jerami Padi Sebagai Penyimpanan Biogas Dengan Variasi Ukuran Mesh - Mursadana, Agus Andika; Ketut Putra Negara, Dewa Ngakan; Sucipta, Made (Teknik Desain Mekanika; Vol 10 No 3 (2022): Juli 2022 : Teknik Desain Mekanika, 2022)
Abstract Simantri is an innovation that develops technology that innovates the community for village progress. Simantri activities include increasing the number of livestock populations, planting area, and the quality of the products produced. Cow dung waste from Simantri can be used as biogas as fuel to turn on the stove. The use of biogas for the wider community has not been optimal due to the limited distribution of biogas. This research is expected to find out the potential utilization of rice straw waste as an adsorbent as a biogas storage medium with the ANG (Adsorbtion Natural Gas) system. The method used is the adsorption of biogas at a storage pressure of 100 psi with 70 grams of activated carbon from rice straw as the adsorbent, the activated carbon was varied with a mesh size of 70-100, 100-200, and 200-500 at an activation temperature of 325oC. The results of the research in biogas storage showed that the highest mass absorption occurred in the 200-500 mesh variation which was able to store 3.5 grams of biogas. Then for testing the biogas content, the highest levels of methane and the lowest carbon dioxide occurred at a mesh variation of 200-500. Keywords: rice straw, biogas, ANG, Carbon Active